COVID-19 and a way forward for restaurants and street food vendors - Shumaila Zeb; Syed Shahwar Hussain; Asma Javed (Cogent Business & Management, 2021)
COVID-19 has had a drastic impact on every field and walk of life. The long-lasting impacts of this pandemic have changed the way businesses used to be conducted and will have a strong impact on business models as well. The main objective of this qualitative study is to investigate the impact of COVID-19 on restaurants and small stalls of street food vendors in Pakistan and to suggest a way forward. A total of 30 interviews were conducted through conference calls. The findings proved that major issues faced by the restaurants are the massive decline in sales, massive layoffs, no economic activity, and no relief from the government. The major changes required in the existing business models highlighted by the interviewees are proper sanitization, changes in the sitting area, change in menus, and the need for innovative ideas to attract the customers back. The study is useful for the restaurants and street food vendors to help them out in this difficult phase and suggest a way forward to them.
Keywords: 650; COVID-19; restaurants; street food vendors